Challenges of talent development in alpine ski racing: a narrative review - Steidl-Müller, L.; Hildebrandt, C.; Raschner, C.; Müller, E. (Journal of Sports Sciences, 2019)
Alpine ski racing is one of the most popular sports in many countries; nevertheless, selection disadvantages and severe injuries result in high dropout rates. In this review we summarize existing knowledge about the specific challenges associated with selection bias and injuries, and their effects on talent development in ski racing.